THE ROLE OF STATE ORGANIZATION POLICY IN TOURISM DEVELOPMENT - Khalikova Lola Nazarovna; Ziyodova Raykhona Jasur kizi (Ta’lim innovatsiyasi va integratsiyasi, 2024)
Abstract: This article gives information about the state policy aimed at improving the tourism sector and its main directions. In the article tourism field state organizations by in order put importance, tourism in the field state of politics main directions and methods, field efficient development and competition environment of formation main principles see will be released. Tourism field development of support modern methods studied too.